2016
DOI: 10.1111/bju.13462
|View full text |Cite
|
Sign up to set email alerts
|

Complications and quality of life in elderly patients with several comorbidities undergoing cutaneous ureterostomy with single stoma or ileal conduit after radical cystectomy

Abstract: The present results show that CU with a single stoma can represent a valid alternative to IC in elderly patients with relevant comorbidities, reducing peri-operative complications without a significant impairment of QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 26 publications
9
85
0
Order By: Relevance
“…Interestingly, our study failed to demonstrate significant differences in terms of perioperative complications between patients with IC or CU. Conversely, Longo et al [23] recently showed in a series of patients aged >75 with relevant comorbidities that singlestoma CU had reduced perioperative complications with no significant impairment of health-related quality of life. In another recent study analyzing the impact of perioperative complications in patients aged >75 years, major complications were reported in 27% of patients who underwent IC and in 36% of those who received CU.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, our study failed to demonstrate significant differences in terms of perioperative complications between patients with IC or CU. Conversely, Longo et al [23] recently showed in a series of patients aged >75 with relevant comorbidities that singlestoma CU had reduced perioperative complications with no significant impairment of health-related quality of life. In another recent study analyzing the impact of perioperative complications in patients aged >75 years, major complications were reported in 27% of patients who underwent IC and in 36% of those who received CU.…”
Section: Discussionmentioning
confidence: 94%
“…In a large single‐center series, the overall long‐term complication rate was reported to be 40.8%, with three neobladder‐related deaths . Furthermore, a recent single‐center study investigating the mortality and morbidity rates of RC, particularly among elderly patients aged >75 years, showed that intraoperative and early postoperative complications occurred in 16 and 43%, respectively, and complications of Clavien grade IVa/V were observed in 10% . As Cookson et al .…”
Section: Rc For Bcg‐unresponsive Diseasementioning
confidence: 92%
“…BCa is the most common malignancy of the urinary tract, the seventh most common cancer in men and the 17th in women (1,(15)(16)(17). Transurethral resection of bladder tumors is the gold standard for removal of BCa, to allow diagnosis and, in many cases, definitive treatment (1,(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Transurethral resection of bladder tumors is the gold standard for removal of BCa, to allow diagnosis and, in many cases, definitive treatment (1,(15)(16)(17). However, tumor may recur or progress to muscle invasive disease and further adjuvant intravesical therapies are often needed (1).…”
Section: Discussionmentioning
confidence: 99%